MODEL PERTUMBUHAN LOGISTIK DENGAN KONTROL OPTIMAL PENYEBARAN DEMAM BERDARAH DENGUE - ., Kartono; ., Widowati; Utomo, Robertus Heri Soelistyo; Tjahjana, Redemtus Heru (MATEMATIKA, 2015)
Controlling of spread of dengue fever was sought by the government together with the people by, among others, campaigning â€œ3M controllingâ€ and eradicating of the vector population using insecticide and threating the infected people. The aim of this research is constructing the optimal control dynamic model by applying several strategies to control the spread of dengue fever. In this paper, the optimal control is constructed by using host logistic growth population model approach and then it is solved by using maximum Pontryagin principle. The results show that in the equilibrium condition, the effect of the control variable u1 (â€œ3M campaigningâ€ and eradicating of the mosquito by using insecticide) is strongly affected by the rate of the direct contact between host population and the infected and susceptible vector whereas the control variable u2 is strongly affected by the number of the infected host population